2019
DOI: 10.3389/fimmu.2019.01950
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Methylation Inhibitor Zebularine Controls CD4+ T Cell Mediated Intraocular Inflammation

Abstract: CD4 + T cell mediated uveitis is conventionally treated with systemic immunosuppressive agents, including corticosteroids and biologics targeting key inflammatory cytokines. However, their long-term utility is limited due to various side effects. Here, we investigated whether DNA methylation inhibitor zebularine can target CD4 + T cells and control intraocular inflammation. Our results showed that zebularine restrained the expression of inflammatory cytokines IFN-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Furthermore, IL-10 expression was investigated in both Th1 and Th17 cells suggesting a regulatory role [22]. Our study also demonstrated that the significant increase of Th17/Th1 phenotype in peak EAU in a monophasic mouse model was only detected in retinal tissues and not dLNs or peripheral blood [23], and suggests an important role of the tissue microenvironment in CD4 + T cell plasticity. Our detection of increased levels of intraocular Th17/Th1 cells in comparison to dLNs could be as a result of the local microenvironment within the eye, which contains a range of cytokines, notably TGF-ß [24].…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, IL-10 expression was investigated in both Th1 and Th17 cells suggesting a regulatory role [22]. Our study also demonstrated that the significant increase of Th17/Th1 phenotype in peak EAU in a monophasic mouse model was only detected in retinal tissues and not dLNs or peripheral blood [23], and suggests an important role of the tissue microenvironment in CD4 + T cell plasticity. Our detection of increased levels of intraocular Th17/Th1 cells in comparison to dLNs could be as a result of the local microenvironment within the eye, which contains a range of cytokines, notably TGF-ß [24].…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, research in mice models on azacitidine and decitabine function found that ZEB promoted Foxp3 expression and CpGs demethylation of the Tregs' upstream enhancer. In addition, human CD4 + ZEB-mediated cells had diminished INF-γ and IL-17A expression [83].…”
Section: Epigenetic Modifiers Of the Foxp3 Locusmentioning
confidence: 97%
“…Nonetheless, an analogue of DAC, named Zebularine, has been characterized and it is active per os [32,33]. However, although Zebularine has been show to downregulate autoimmune responses in experimental autoimmune uveitis [34], it has not reached the clinical development phase and complete preclinical development is required to be tested in humans.…”
Section: Discussionmentioning
confidence: 99%